2023
DOI: 10.1039/d2ra07029d
|View full text |Cite
|
Sign up to set email alerts
|

N-oxide ligands for selective separations of lanthanides: insights from computation

Abstract: N-oxide ligands, combined with pyridinic N groups, are predicted to offer attractive La(iii)/Ln(iii) selectivities for rare-earth separations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 37 publications
2
18
2
Order By: Relevance
“…The FTIR spectra of neat and regenerated IL are almost identical (Figure S5). In the 13 C and 1 H NMR spectra (Figure 2), no residual acetic acid and acetonitrile was found in the regenerated IL. Generally, the proton signal of acetic acid lies between 10 and 15 ppm, and that of acetonitrile near 2 ppm [52,53].…”
Section: Regeneration Of the Reacted Ionic Liquidmentioning
confidence: 99%
See 3 more Smart Citations
“…The FTIR spectra of neat and regenerated IL are almost identical (Figure S5). In the 13 C and 1 H NMR spectra (Figure 2), no residual acetic acid and acetonitrile was found in the regenerated IL. Generally, the proton signal of acetic acid lies between 10 and 15 ppm, and that of acetonitrile near 2 ppm [52,53].…”
Section: Regeneration Of the Reacted Ionic Liquidmentioning
confidence: 99%
“…The samples were dissolved in deuterated DMSO-d6 and filled in an NMR tube. Measurements were performed on a Bruker Avance (Leipzig, Germany) Neo WB 300 MHz NMR spectrometer at resonance frequencies of 300 MHz for 1 H and 75.5 MHz for 13 C spectra. The chemical shifts were referenced externally according to tetramethylsilane (TMS) and were calibrated with 10% ethylbenzene in CDCl 3 as external reference.…”
Section: Synthesis Of [Bdmim][oac]mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to a large number of reports available in the literature, which target the selective separation of trivalent actinides over lanthanides utilizing several N donor or S donor ligands, attempts have been made to use mixed donor ligands containing O and N atoms for enhanced selectivity of actinides over lanthanides. It is anticipated that the cooperative complexation of multifunctional ligands can be far more efficient than the ligands containing one ligating site. In this context, nitrilotriacetamide (NTAamide, Figure ) ligands, having both >CO oxygen atoms and a central nitrogen atom, have been investigated for their selective complexation and extraction of trivalent actinides over lanthanides. , Initial studies with N,N,N′,N′,N″,N″ -hexa- n -octyl nitrilotriacetamide (HONTA) as the extractant have shown that Am 3+ is 23.6 times more extracted than the lanthanides .…”
Section: Introductionmentioning
confidence: 99%